Milk and Dairy Consumption and Its Relationship With Abundance of Lactobacillus crispatus in the Vaginal Microbiota: Milk Intake and Vaginal Lactobacillus - Moura, Gabriela B.; Silva, Márcia G. [UNESP]; Marconi, Camila [UNESP] (Wolters Kluwer, 2023)
Objectives Diet habits, such as low milk and dairy intake, have been associated with bacterial vaginosis. Thus, the authors compared vaginal Lactobacillus crispatus abundances in women with different molecularly defined community state types (CSTs) according to the consumption of milk and/or dairy products. Methods A total of 516 women from the 5 geographic regions of Brazil were included. Participants were interviewed with a structured questionnaire for assessment of milk and/or dairy intake. Vaginal samples were used for sequencing of V3-V4 regions of the 16S ribosomal RNA gene for further determination of L. crispatus relative abundance (RA) and clustering into 1 of the 5 CSTs (CSTI-CSTV), as firstly described by Ravel et al. (2011). The nonparametric Mann-Whitney test was used to compare L. crispatus RA within the most representative CSTs (L. crispatus-dominant CSTI, Lactobacillus iners-dominant CSTIII, and Lactobacillus-depleted CSTIV) in this population, according to the frequency of milk and/or dairy intake. Results The prevalence of CSTI was 33.3% (n = 172), CSTIII was 39% (n = 201), and CSTIV was 27.7% (n = 143). Among the participants with CSTIII, higher L. crispatus RA was observed for those who reported milk/dairy intake (median = 0.02; interquartile range = 0.01-0.09) than those with no consumption (median = 0.01; interquartile range = 0-0.03) (p =.03). Such difference was not observed for participants with CSTI and CSTIV. Conclusions Women with vaginal microbiota dominated by L. iners who consume milk and/or dairy present increased abundances of L. crispatus. Therefore, they could benefit from L. crispatus protective properties conferring greater temporal microbiota stability and, consequently, increased protection against infections.
Keywords: dairy; diet; lactobacillus; Lactobacillus crispatus; Lactobacillus iners; milk; vaginal microbiota